2017
DOI: 10.12659/msm.904474
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Combined with Treadmill Training Improves Walking Performance in Post-Stroke Patients: A Randomized Controlled Trial

Abstract: BackgroundStroke is characterized by an asymmetrical gait pattern that causes poor stability and reduces overall activity levels. The aim of this study was to investigate the effect of whole-body vibration combined with treadmill training (WBV-TT) on walking performance in patients with chronic stroke.Material/MethodsThirty ambulatory chronic stroke patients were randomly allocated to the WBV-TT group or the treadmill training (TT) group. The participants in the WBV-TT group performed 6 types of exercises on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 28 publications
1
50
0
1
Order By: Relevance
“…Finally, 63 full-text articles were assessed for eligibility with 17 not accepted: five because training lasted <4 weeks, six because they were not RCT, four because there were no walking outcomes, one because it combined WBV training with non-physical therapy and one for comparing WBV training combined with another intervention not provided in the control group (meaning that not only WBV effects were measured). Thus, 46 articles were ultimately included in this systematic review (9, 2769, 71, 72). A summary of the study selection is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 63 full-text articles were assessed for eligibility with 17 not accepted: five because training lasted <4 weeks, six because they were not RCT, four because there were no walking outcomes, one because it combined WBV training with non-physical therapy and one for comparing WBV training combined with another intervention not provided in the control group (meaning that not only WBV effects were measured). Thus, 46 articles were ultimately included in this systematic review (9, 2769, 71, 72). A summary of the study selection is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 14 to 159 participants, with a mean age of 60.9 ± 20.0 years, varying from 7.9 years to 83.2 years. With regard to the adult population, 16 studies evaluated the effects of WBV in the elderly ( n = 59.8 ± 35.4 subjects) (9, 3032, 36, 40, 44, 45, 50, 53, 55, 56, 59, 62, 64, 69), four in patients with Chronic Obstructive Pulmonary Disease (COPD) ( n = 42.5 ± 16.7 subjects) (57, 61, 65, 71), seven in patients with stroke ( n = 46.1 ± 27.2 subjects) (28, 35, 38, 51, 54, 67, 72), four in patients with osteoarthritis (OA) ( n = 32.2 ± 11.9 subjects) (29, 33, 63, 68), three in postmenopausal women ( n = 40.3 ± 12.5 subjects) (48, 58, 66), two in patients with multiple sclerosis ( n = 29.5 ± 6.3 subjects) (34, 39) and one in patients with the following pathologies: incomplete cervical spinal injury (47), pulmonary arterial hypertension (42), lung transplantation (43), idiopathic Parkinson's disease (41), total knee arthroplasty (49) and cerebral palsy (27) ( n = 30.0 ± 26.4 subjects). With regard to the child population, two studies evaluated the effects of WBV in cerebral palsy (37, 60), one in patients with osteogenesis imperfect (46) and one in patients with spastic diplegia or quadriplegia forms of cerebral palsy (52) ( n = 22.5 ± 5.9 subjects).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the neuromodulatory effects of vibration on spinal reflex excitability, there is evidence that vibration activates spinal central pattern-generating circuits that underlie the generation of locomotor output [16][17][18]. Early evidence indicates that WBV may improve walking function in persons with SCI [19] and appears to augment the effects of locomotor training in persons with stroke [20]. While WBV is being used in clinical settings to treat individuals with neurologic conditions, there is little evidence available to offer guidance regarding parameters related to frequency and duration of WBV dose.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that gait speed was improved by increasing stride length. In most reports aimed at improvement of gait speed, both stride length and cadence were improved together with improvement of gait speed [27][28][29][30]. However, the relationship between gait speed and stride length or cadence was rarely reported, though the relationship is important to let clinicians know how the intervention affected their patients' gait pattern.…”
Section: Discussionmentioning
confidence: 99%